2001
DOI: 10.1046/j.1442-2042.2001.00314.x
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of renal cell carcinoma: A nation‐wide survey in Japan in 1997

Abstract: Background: The present study was conducted to investigate the incidence of renal cell carcinoma by sex, age group and different regions in Japan. Methods:The survey was conducted from the beginning of January 1997 to the end of December 1997. A total of 1306 Institutions in all 47 prefectures throughout Japan were requested to register cases.Results: There were 6358 persons with renal cell carcinoma, consisting of 4372 men and 1986 women. The age-specific incidence rates showed a peak in the age group of 65-7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 16 publications
0
23
0
Order By: Relevance
“…Lifestyle and dietary habits, that is a higher prevalence of smoking, greater intake of dairy products, lesser intake of vitamin C and the highest prevalence of hypertension in Japan for Hokkaido have been discussed in the previous report. 5 It is imperative to determine whether the incidence of RCC is increasing due to changes in environmental factors and if the currently available early detection of RCC is able to decrease death from this disease. Although it is difficult to determine whether the incidence of RCC is truly rising using a simple comparison with previous surveys conducted prior to the current study, 5 there are several reports indicating recent increases in RCC incidence.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Lifestyle and dietary habits, that is a higher prevalence of smoking, greater intake of dairy products, lesser intake of vitamin C and the highest prevalence of hypertension in Japan for Hokkaido have been discussed in the previous report. 5 It is imperative to determine whether the incidence of RCC is increasing due to changes in environmental factors and if the currently available early detection of RCC is able to decrease death from this disease. Although it is difficult to determine whether the incidence of RCC is truly rising using a simple comparison with previous surveys conducted prior to the current study, 5 there are several reports indicating recent increases in RCC incidence.…”
Section: Discussionmentioning
confidence: 99%
“…5 It is imperative to determine whether the incidence of RCC is increasing due to changes in environmental factors and if the currently available early detection of RCC is able to decrease death from this disease. Although it is difficult to determine whether the incidence of RCC is truly rising using a simple comparison with previous surveys conducted prior to the current study, 5 there are several reports indicating recent increases in RCC incidence. 1,2,15,16 These increases may be partly due to increased cancer risk resulting from an aging population, in addition to the development and increased use of improved diagnostic imaging procedures.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In Japan, Satoh et al [11] reported that 38 (0.6%) out of 6201 dialysis patients [12] reported that 44 patients (1.7%) were pathologically diagnosed with renal cell carcinoma in 2,624 dialysis patients between 1993 and 2004. These incidences of kidney cancer among dialysis patients appear higher than the incidence of general population (i.e., 7.1/100,000 for males and 3.1/100,000 [36]). On the other hand, the annual nation-wide questionnaire studies between 1982 and 2004 conducted by the Japanese Society for Dialysis Therapy revealed that hemodialysis patients had a significantly higher risk of renal cell cancer than the general population(p<0.05) [13].…”
Section: Risk Factors Medical Conditionsmentioning
confidence: 91%